Partisan Schemata in Biased Interpretation of Electoral Proposals and Political Candidate Evaluation. Issue 4 (2nd October 2019) - Falkowski, Andrzej; Cwalina, Wojciech
Abstract : Both a party proposals and the politician's personality are among the important determinants of their success in the political market. Studies on the perception of the surrounding physical and social reality clearly demonstrate that the evaluation of experienced objects and events depends not only on the properties of the perceived stimulus but also on the external context, made up of the surrounding stimuli and events, and on the internal context, consisting of the cognitive schemata of the individuals. Two performed experiments covering the same political party proposals and the same personal profile of a politician demonstrate that the evaluation of that party and politician, if presented in different political contexts, depends on the politician's party affiliation and the voters partisanship. The results of the research lead to the hypotheses on political tolerance which depends on the political orientation of the voters and is subject to modification by the political object evaluated, that is, the party (a formally organized group) or the politician (a person).